2016
DOI: 10.1002/ss.20188
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Issues and Models in College Mental Health Services

Abstract: 2This chapter provides a brief overview of the psychological issues facing today' s college students, information about students receiving mental health services, and an evidence-based model describing the practice and functions of today' s counseling centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Included in this definition are illnesses such as bipolar disorders, schizophrenia, developmental disorders, and depression. Approximately 19.4% of young adults between the ages of 18 and 25 years experience some form of mental health disorder such as depression or anxiety (Locke, Wallace, & Brunner, ). This is not surprising given that the 2016 CIRP Freshman Survey (a national survey of college first‐year students), found that 41% of incoming full‐time freshmen reported that as high school seniors they were “frequently” overwhelmed by all they had to do and 47% anticipated seeking personal counseling while in college (Eagan et al., ).…”
mentioning
confidence: 99%
“…Included in this definition are illnesses such as bipolar disorders, schizophrenia, developmental disorders, and depression. Approximately 19.4% of young adults between the ages of 18 and 25 years experience some form of mental health disorder such as depression or anxiety (Locke, Wallace, & Brunner, ). This is not surprising given that the 2016 CIRP Freshman Survey (a national survey of college first‐year students), found that 41% of incoming full‐time freshmen reported that as high school seniors they were “frequently” overwhelmed by all they had to do and 47% anticipated seeking personal counseling while in college (Eagan et al., ).…”
mentioning
confidence: 99%
“…On the basis of informal feedback from our participants, we recommend offering brief booster sessions either at 1-month postintervention or once every term to ensure maintenance of skills. This type of brief intervention sits well with the preventive and educational roles taken on by college counseling centers (e.g., Locke et al, 2016). In addition, ACT's emphasis on personal values seems to be suitable for this age group, being that its members are in a process of self-exploration.…”
Section: Implications For College Counselingmentioning
confidence: 79%
“…4 Despite the fact that college campus counseling centers have been found to be extremely helpful in assisting students, the students who receive those services are typically self-referred. 5 Many college campuses provide some mental health screening and have even used online forums and social media to reach more students, but again, participants in such screening events are typically self-referred. 6 One way to increase awareness of the potential need for mental health services among students is to implement universal screening programs where all students are provided with an opportunity to engage in mental health screening and receive appropriate feedback.…”
Section: Introductionmentioning
confidence: 99%